A Step toward NRF2‐DNA Interaction Inhibitors by Fragment‐Based NMR Methods. (8th October 2021) - Brüschweiler, Sven; Fuchs, Julian E.; Bader, Gerd; McConnell, Darryl B.; Konrat, Robert; Mayer, Moriz
Abstract: The NRF2 transcription factor is a key regulator in cellular oxidative stress response, and acts as a tumor suppressor. Aberrant activation of NRF2 has been implicated in promoting chemo‐resistance, tumor growth, and metastasis by activating its downstream target genes. Hence, inhibition of NRF2 promises to be an attractive therapeutic strategy to suppress cell proliferation and enhance cell apoptosis in cancer. Direct targeting of NRF2 with small‐molecules to discover protein‐DNA interaction inhibitors is challenging as it is a largely intrinsically disordered protein. To discover molecules that bind to NRF2 at the DNA binding interface, we performed an NMR‐based fragment screen against its DNA‐binding domain. We discovered several weakly binding fragment hits that bind to a region overlapping with the DNA binding site. Using SAR by catalogue we developed an initial structure‐activity relationship for the most interesting initial hit series. By combining NMR chemical shift perturbations and data‐driven docking, binding poses which agreed with NMR information and the observed SAR were elucidated. The herein discovered NRF2 hits and proposed binding modes form the basis for future structure‐based optimization campaigns on this important but to date 'undrugged' cancer driver. Abstract : Key regulator modulation : In a fragment‐based ligand screening approach two small‐molecule binders to the key pro‐oncogenic cancer driver NRF2 were discovered. The structure‐activity relationship of the initial fragment hits was established by a SAR‐by‐catalogue exploration. The binding pose of one the compounds, which binds to a region overlapping with the DNA binding site, was determined by a chemical shift perturbation restrained docking simulation which can serve as a starting point in a hit‐to‐lead campaign.